2018
DOI: 10.1103/physrevd.97.032014
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of total and differential cross sections of neutrino and antineutrino coherent π± production on carbon

Abstract: Neutrino induced coherent charged pion production on nuclei,ν μ A → μ AE π ∓ A, is a rare inelastic interaction in which the four-momentum squared transferred to the nucleus is nearly zero, leaving it intact. We identify such events in the scintillator of MINERvA by reconstructing jtj from the final state pion and muon momenta and by removing events with evidence of energetic nuclear recoil or production of other final state particles. We measure the total neutrino and antineutrino cross sections as a function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 69 publications
(111 reference statements)
3
27
0
Order By: Relevance
“…GENIE uses the Rein-Sehgal coherent pion production model [36,37], including the effect of lepton masses in the cross-section calculation. MINERvA has found that the RS coherent pion production model needs to be suppressed by ∼ 50% at T π < 500 MeV to agree with data [27]. This correction also moves the shape of the T π spectrum closer to the predictions of the Berger-Sehgal coherent model [38].…”
Section: Pion Production In Geniementioning
confidence: 83%
See 1 more Smart Citation
“…GENIE uses the Rein-Sehgal coherent pion production model [36,37], including the effect of lepton masses in the cross-section calculation. MINERvA has found that the RS coherent pion production model needs to be suppressed by ∼ 50% at T π < 500 MeV to agree with data [27]. This correction also moves the shape of the T π spectrum closer to the predictions of the Berger-Sehgal coherent model [38].…”
Section: Pion Production In Geniementioning
confidence: 83%
“…The twoparticle two-hole process is simulated using the Valencia model [11,25]. MINERvA currently uses a modification of v2.8.4 [19,26,27] with an increased rate for the Valencia two-particle two-hole process; that modification is not used here. An important difference in single pion production between v2.8.x and v2.12.x is the angular distributions of single pion events in the Rein-Sehgal model, discussed below.…”
Section: Pion Production In Geniementioning
confidence: 99%
“…The charged current version serves mainly as a background to µ + µ − tridents, but can also appear as a background for e ± µ ∓ tridents for incoming electron neutrinos or antineutrinos. It has been studied before at MiniBooNE [60], MINERνA [61,62], T2K [28,63], and for the first time in LAr at ArgoNeuT [64]. This process has a very distict low 4-momentum transfer to the nucleus |t| [61], but a much flatter distribution in invariant mass if compared to trident.…”
Section: C1 Pion Productionmentioning
confidence: 99%
“…The excess in sideband 4 is attributed to coherent events, allowing the normalization of that background to float in the background fits, which are performed by computing a χ 2 summed over distributions in each of the four sidebands. Because MINERνA studies of both neutral-current diffractive [28] and charged-current coherent π 0 production [29] have found significant discrepancies with GENIE predictions that vary with energy, the normalization of the coherent background is allowed to vary separately for each of the six electron energy bins. For the other three backgrounds, the fit includes a single normalization factor that is constant with reconstructed energy.…”
Section: Background Subtractionmentioning
confidence: 99%